Plan de negocios para la creación de un centro especializado en la imagen y el cuidado personal de niños y niñas en la ciudad de Quito - Hidalgo Tapia, Nicole Estefanía (2015)
This business plan has been develop to meet the need for personal care services for children in the city of Quito. Fashion Kids will offer more than traditional beauty services; it will provide a unique experience through specialized services based on the kids needs, within a safe environment and a value added called fun. It will also seek to contribute positively to educating children about the importance of hygiene in their lives, through workshops and self-care tips. According to the expert in the early childhood, María Alexandra Clavijo (2014), children need to receive services according to their needs, which are different from those of an adult. In addition, if the kid practices a culture of hygiene during its childhood, he will maintain the good habits throughout his live. The target market of this project are children from 6 months to 11 years old, who live in the urban area of Quito and belong to the upper middle class...